Inflammatory Injury to the Neonatal Brain – What Can We Do? - Ofek-Shlomai, Noa; Berger, Itai (Frontiers in Pediatrics, 2014)
Abstract Perinatal brain damage is one of the leading causes of life long disability. This damage could be hypoxic-ischemic, inflammatory or both. This mini-review discusses different interventions aiming at minimizing inflammatory processes in the neonatal brain, both before and after insult. Current options of anti-inflammatory measures for neonates remain quite limited. We describe current anti-inflammatory intervention strategies such as avoiding perinatal infection and inflammation, and reducing exposure to inflammatory processes. We describe the known effects of anti-inflammatory drugs such as steroids, antibiotics, and indomethacin, and the possible anti-inflammatory role of other substances such as IL-1receptor antagonists, erythropoietin, caffeine, estradiol, insulin like growth factor and melatonin as well as endogenous protectors, and genetic regulation of inflammation. If successful, these may decrease mortality and long term morbidity among term and preterm infants.